PENGARUH PEMBERIAN TEPUNG LIMBAH LABU KUNING (Cucurbita moschata) DALAM RANSUM TERHADAP PERSENTASE KARKAS, POTONGAN KOMERSIL DAN LEMAK ABDOMINALPADAAYAM PEDAGING - Pakasi, Mianty C; Mandey, J S; Kowel, Y H.S; Regar, M N (ZOOTEC, 2020)
THE EFFECT OF YELLOW PUMPKIN (Cucurbita moschata) MEALIN THE DIET ON THE CARCASS, CARCASS COMMERCIAL CUTTING AND ABDOMINAL FAT OF BROILER CHICKENS. This study aims to determine the effect of pumpkin (Cucurbita moschata) waste in the diet on carcass percentage, commercial cutting of carcass (breasts, thighs, wings) and abdominal fat in broilers. The study used 100 unsexed D.O.C. of broilers, strain Cobb. The experiment used a completely randomized design (CRD) consisting of 4 treatments and 5 replications. The follow-up test used was Honest Real Difference (BNJ). The treatment arrangements are as follows: R0 = Basal Diet (BD) 100% + 0% Yellow Pumpkin Meal (YPM); R1 = BD 95% + 5% YPM; R2 = BD 90% + 10% YPM; R3 = BD 85% + 15% YPM. The results showed that carcass weight and carcass percentage in treatment R0, R1, R2 were significantly higher than treatment R3, but between treatments R0, R1, R2 were not significantly different. The commercial section of the right chest of treatment R1, R2, R3, was significantly higher than the R0 treatment, but between treatments R1, R2, R3 were not significantly different, while on the left chest showed that treatments R0, R2, R3 were significantly higher than R1, however, between treatments R0, R2, R3 were not significantly different. Thigh and wing sections, and abdominal fat percentage showed no significant differences. Based on the results, it can be concluded that15% pumpkin waste mealin broiler diet has a good effect on body weight growth, carcass percentage and part of the commercial cutting percentage of broiler carcass.